Long-term consequences of prenatal stress and neurotoxicants exposure on neurodevelopment - Antonelli, Marta Cristina (2017)
There is a large consensus that the prenatal environment determines the susceptibility to pathological conditions later in life. The hypothesis most widely accepted is that exposure to insults inducing adverse conditions in-utero may have negative effects on the development of target organs, disrupting homeostasis and increasing the risk of diseases at adulthood. Several models have been proposed to investigate the fetal origins of adult diseases, but although these approaches hold true for almost all diseases, particular attention has been focused on disorders related to the central nervous system, since the brain is particularly sensitive to alterations of the microenvironment during early development. Neurobiological disorders can be broadly divided into developmental, neurodegenerative and neuropsychiatric disorders. Even though most of these diseases share genetic risk factors, the onset of the disorders cannot be explained solely by inheritance. Therefore, current understanding presumes that the interactions of environmental input, may lead to different disorders. Among the insults that can play a direct or indirect role in the development of neurobiological disorders are stress, infections, drug abuse, and environmental contaminants. Our laboratories have been involved in the study of the neurobiological impact of gestational stress on the offspring (Dr. Antonelli´s lab) and on the effect of gestational exposure to toxicants, mainly methyl mercury (MeHg) and perfluorinated compounds (PFCs) (Dr. Ceccatelli´s lab). In this focused review, we will review the specialized literature but we will concentrate mostly on our own work on the long term neurodevelopmental consequences of gestational exposure to stress and neurotoxicants.